The Use of Impella 2.5 in Severe Refractory Cardiogenic Shock Complicating an Acute Myocardial Infarction. (February 2015) - CASASSUS, FREDERIC; CORRE, JEROME; LEROUX, LIONEL; CHEVALEREAU, PIERRE; FRESSELINAT, AURELIE; SEGUY, BENJAMIN; CALDERON, JOACHIM; COSTE, PIERRE; OUATTARA, ALEXANDRE; ROQUES, XAVIER; BARANDON, LAURENT
<x xml:space="preserve">Abstract</x> Objectives To investigate the outcome of patients with acute myocardial infarction (AMI) complicated by refractory cardiogenic shock (CS) who underwent mechanical circulatory support with Impella 2.5. Background AMI complicated by CS remains a highly fatal condition. A potent and minimally invasive left ventricular assist device might improve patient outcomes. Methods We analyzed the procedural characteristics and outcomes of 22 consecutive patients who underwent, between July 2008 and December 2012, a percutaneous coronary intervention and Impella 2.5 support for AMI complicated by CS refractory to first‐line therapy with inotropes and/or Intra‐aortic balloon pump. Results In this analysis, patients were relatively young with a mean age of 57.9 ± 11.6 year old and 59.1% were male. The majority of patients (77.3%) were admitted in CS and 40.9% sustained cardiac arrest prior to admission. Hemodynamics improved significantly upon initiation of support, end‐organ and tissue perfusion improved subsequently demonstrated by a significant decrease in lactate levels from 6.37 ± 5.3 mmol/L to 2.41 ± 2.1 mmo/L, (P = 0.008) after 2 days of support. Thirteen (59.1%) patients were successfully weaned‐off Impella 2.5 and 4 (18.2%) were transitioned to another device. We observed a functional recovery of the left ventricle when compared to baseline (43 ± 10% vs. 27 ± 9%, P < 0.0001). The survival rate at 6 months and 1 year was 59.1% and 54.5%, respectively. Conclusion Impella 2.5 was initiated as a last resort therapy to support very sick patients with refractory CS after failed conventional therapy. The use of the device yielded favorable short and mid‐term survival results with recovery being the most frequently observed outcome. (J Interven Cardiol 2015;28:41–50)